UNITED NATIONS PEACE OPERATIONS ON STATE-BUILDING AND GOVERNANCE IN POST-CONFLICT AFRICAN STATES: A CASE STUDY OF SOUTH SUDAN - Abraham Ename Minko (Margalla Papers)
This study examines the role of United Nations (UN) peace missions in state-building and governance when recovering from conflicts, focusing on South Sudan grappling with post-independence challenges in 2011 due to ongoing violence and political turmoil that disrupted governance efforts. The United Nations Mission in South Sudan (UNMISS) is crucial in promoting peace and rebuilding the state structures. The study delves into the roles and shortcomings of UNMISS in fostering stability and curbing violence while bolstering governance structures. It also investigates the dynamics among the UN mission's local governance entities and international stakeholders by employing a qualitative methodology approach to shed light on achievements and hurdles, with suggestions to boost the efficiency of upcoming UN peacekeeping ventures in akin scenarios. The results emphasise the importance of collaboration between actors and domestic organisations to uphold lasting peace and governance in African nations emerging from conflict.